Preferences of rural youth towards fisheries vocations in Doda District of Jammu Division, Jammu and Kashmir, India - Paul, Narinder; Jha, G. N.; Charak, A. S. (Indian Journal of Fisheries, 2021)
The preferences of rural youth towards different fisheries vocations have been assessed using the Thurstone paired comparison technique. Six major fisheries vocations which trainings were imparted to the rural youth by the Krishi Vigyan Kendra, Doda during 2016-17, 2017-18 and 2018-19 were identified. A sample of 94 rural youth was randomly drawn from Â 940 rural youth who attended various awareness programmes, training programmes and exposure visits organised by KVK Doda independently or in collaboration with National Fisheries Development Board (NFDB), Hyderabad and Directorate of Coldwater Fisheries Research (DCFR), Bhimtal during these three years. Trout culture with the highest scale value of 0.563 was the most preferred fishery vocation by the rural youth and aquarium making was the least preferred with scale value of 0.00. Other vocations viz., carp culture, fish seed production, ornamental fish production and fish feed production were found in between this continuum with varying degrees of the scale distances. The average value of Absolute Discrepancy (AD) estimated was 0.009, which implies that the calculated scale values of the various fisheries vocations had very high level of consistency.Key words: Fisheries, Paired comparison, Rural youth, Thurstone paired comparison technique, Training, Vocation